Role of Militancy in Intensifying the Negative Attitude Towards Secondary School Education: Gendered and Religious Dimensions (Journal of Asian Development Studies, 2023)
The deteriorating impact of militancy on education is inevitable. For two decades, the recently merged tribal districts are examples of the deterioration brought up by militancy. Framed under a mixed-method research design, this study aims to determine the impact of militancy on education, i.e., the impact of militancy on secondary-level education. The study locale was the recently merged tribal districts of Khyber Pakhtunkhwa, Pakistan. Simple random and purposive sampling techniques have been utilized to select samples from the population. Sample size has been determined through the Uma Sekaran sample size table, whereas in qualitative data collection, sample size was determined through the saturation point technique. A structured questionnaire and an interview was prepared to collect information from the sampled respondents. The reliability and validity of the questionnaire were tested before data collection. A total of 405 samples were taken, whereby 397 were for survey and 8 for focus group discussion. It is concluded that the situation of the locality was not feasible for good education in the locality prior to and during the case of war. Normative structure (Pakhtunwali), religious misperceptions, gendered-oriented barriers, lack of investment, and lack of focus from the government were a few notable barriers to secondary-level education in the study’s locale. The militancy intensified these barriers and led to further deterioration of school-level education. There were specific impacts of militancy on education in the study’s area, like attacks on schools, physical destruction of school buildings, migration of families, harassment of females to not go to schools and harassment of teachers, etc.